Implementasi Akad Rahn Produk KUR Syariah di Pegadaian Syariah UPS Senenan Berdasarkan Fatwa DSN-MUI No. 68/DSN-MUI/III/2008 Rahn Tasjily - Maulana Ichsan Firmansyah; Dahruji Dahruji (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
Pegadaian Syariah are part of the LKNB sector in charge of providing loans with collateral of general value in some of its products. Product categories owned by PT. Pegadaian Syariah include the rahn category, arrum category, savings category and installment category. In addition, claims from PT. Pegadaian Syariah that explain their products are in accordance with sharia principles. Some of the latest released products are Sharia KUR which has a similar implementation to Arrum BPKB but with claims without collateral (guarantee). This is reinforced by a letter of agreement that states the use of the rahn tasjily contract in the Sharia KUR agreement letter and not the qardh contract which in fact from the rahn tasjily contract requires a letter or certificate underlying the collateral as a condition of the implementation of the contract. Thus, there are problems arising from the application of the appropriate rahn tasjily contract or vice versa. The method used in this study is juridical normative (legal research). The results of the study explained that KUR Syariah and Arrum BPKB proved to be in accordance with its implementation with sharia principles. The conclusion obtained that PT. Pegadaian Syariah must explain frankly to customers the Sharia KUR products that make business assets as collateral and without claims that the product is without collateral (guarantee) with its implementation equivalent to Arrum BPKB products.